Inflammatory Bowel Disease-Experience of a Pediatric Gastroenterology Unit - Nascimento, J (2013)
Inflammatory bowel disease, especially Crohn disease, had increased in the last five decades. We analyzed all the patients of our unit diagnosed with the disease between 2001-2012 but we just considered the patients who respected the Porto criteria to define IBD at presentation. We diagnosed 51 children and adolescents with the disease. Crohn disease was responsible for 62.7% of cases, ulcerative colitis for 31.4% and indeterminate colitis for 5.9%. Considering the 4 different periods of time (2001-2003/2004-2006/2007-2009 and 2010-2012), we observed and increase in the number of cases, but a decrease in the time from onset of symptoms to diagnosis. Our medical approach with tumor necrosis factor antagonists was reserved for severe disease cases and to spare patients from adverse effects of purine analogues and corticosteroids. Mucosal healing and remission of the disease was achieved in all of the patients under biologic therapy and no serious or life-threating event was reported with their use.